2019
DOI: 10.1161/hypertensionaha.118.12740
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Blood Pressure Measured by Home Blood Pressure Monitoring as an Independent Predictor of Cardiovascular Events in General Practice

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 32 publications
1
104
2
3
Order By: Relevance
“…The nighttime BP measured by ABPM is a well‐known cardiovascular risk factor . In that study, nighttime SBP measured by home BP was slightly higher by 2.6 ± 13.4 mm Hg than nighttime BP measured by ambulatory BP ( P < .001).14 Even with this relatively high SD (13.4 mm Hg) of the difference,14 we recently demonstrated that nighttime SBP measured by home BP monitoring was significantly and independently associated with organ damage at baseline and with the risk of new‐onset cardiovascular events during the follow‐up period …”
Section: Discussionmentioning
confidence: 82%
“…The nighttime BP measured by ABPM is a well‐known cardiovascular risk factor . In that study, nighttime SBP measured by home BP was slightly higher by 2.6 ± 13.4 mm Hg than nighttime BP measured by ambulatory BP ( P < .001).14 Even with this relatively high SD (13.4 mm Hg) of the difference,14 we recently demonstrated that nighttime SBP measured by home BP monitoring was significantly and independently associated with organ damage at baseline and with the risk of new‐onset cardiovascular events during the follow‐up period …”
Section: Discussionmentioning
confidence: 82%
“…The J‐HOP study used a specific HBPM device that automatically measured nocturnal home BP during sleep. Key findings were as follows: (a) morning BP is a more important risk factor of stroke than evening BP; (b) day‐by‐day home BPV is significant predictor of cardiovascular events independent of the average of home BP level; and (c) nocturnal home BP is a risk factor for cardiovascular events independent of office and morning home BP . The HONEST study, the largest nationwide Japanese observational trial, confirmed morning home BP as a strong predictor of both coronary artery disease and stroke events, and showed that morning home SBP <125 mm Hg was associated with minimal risk of cardiovascular events in high‐risk patients with diabetes or history of stroke .…”
Section: Hope Asia Networkmentioning
confidence: 93%
“…A recent study also demonstrated that morning home BP was more reproducible and better correlated with vascular indices than ambulatory BP . To date, there have been five general practitioner‐based home BP cohort studies (Table ), including the HOMED‐BP (Hypertension Objective Treatment Based on Measurement by Electrical Devices of Blood Pressure) study, the J‐HOP (Japan Morning Surge‐Home Blood Pressure) study, and the HONEST (Home Blood Pressure Measurement With Olmesartan Naive Patients to Establish Standard Target Blood Pressure) study . All of these showed that morning home BP was a better predictor of cardiovascular events than office BP.…”
Section: Hope Asia Networkmentioning
confidence: 99%
“…This device automatically measures BP at fixed intervals during sleep using a cuff placed on the patient's arm just before going to bed; BP data are stored in the device memory. It was used to monitor nighttime BP in the J‐HOP study, which showed that self‐measurement of nighttime home BP was feasible and recorded BP values similar to those obtained with ABPM . Data from J‐HOP also showed that nighttime home BP was a reliable indicator of target organ damage, even more so than nighttime ABPM determined using ABPM .…”
Section: Development Of Nocturnal Hbpm Devices and Evidencementioning
confidence: 97%